Reoptimalisasi Perlindungan Hukum Saksi Pelapor (Whisteblower) Dalam Tindak Pidana Korupsi - Gunawan, Arifin Faqih; Meliana, Yang (VIVA THEMIS, 2024)
The protection of whistleblower witnesses (whistleblower) in handling corruption crimes is still an unresolved problem to date. Referring to the LPSK report, there was a rapid increase in the number of complaints in 2021, with the number of corruptions also increasing and requiring immediate resolution. Amid the complexity of these demands, both the LPSK and the KPK have not been able to effectively provide guaranteed protection for witnesses reporting corruption crimes. As a result, there are still many cases that cause victims, whether whistleblower witnesses who died, were criminalized, or received threats and intimidation. In fact, in criminal procedural law in Indonesia, witness statements are part of valid evidence. For this reason, the government needs to increase efforts to protect whistleblower witnesses as mandated in Law No.13 of 2006 concerning Witness and Victim Protection. This research uses juridical-normative methods, and seeks to present solutions in policy making to optimize efforts to protect witnesses reporting corruption crimes in Indonesia.